PENERAPAN MEDIA KANTONG BILANGAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PENJUMLAHAN BILANGAN PADA TEMA “BENDA, HEWAN DAN TANAMAN DI SEKITARKU” KELAS 1 MI NURUL YAQIN GADING PROBOLINGGO - Kafihatul Jalaliyah; Muhammad Hanief; Khoirul Asfiyak (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractThe background of this researce is the low students learning outcomes in the sum of numbers. The purpose of this study is to describe the application of number bag media to improve student learning progres in the sum of numbers in first class Islamic Elementary School Nurul Yaqin Gading Probolinggo. The researcher as teacher or giver of action. This research uses a type of classroom action research. This research was applied in 2 cycles. As results obtained from the application of number bag media in cycles 1 and 2 are the increase of student learning progres. At first the average value of students in the pre test was 68.7 with a percentage of completeness of 46.7%, while in the first cycle the average student learning progres was 76.7 with the percentage of completeness being 66.7%, and on second cycle average the student learning progres are 89.3 with the percentage of completeness increase to 93.3%. Based on student learnig progres that have been obtained in first cycles and second cycles it can be summarize that the application of number bag media has been successful, because student learning progres in the sum of the numbers on the theme are initially classified as low but have increased with the results indicator that is equal to 93.3%.Keyword: Number bag, Learning outcomes, Addition